Efektifitas Penyuluhan Kesehatan Menggunakan Media Video Terhadap Pengetahuan Remaja Putri Tentang SADARI di SMA Negeri 1 Karang Intan - Misna Tazkiah; Ince Fitriah (HB PRESS, 2020)
The incidence of breast cancer from year to year is increasing. This is influenced by the low knowledge of young women regarding BSE examination. Efforts to increase the knowledge of young women one of them through self-awareness counseling, conducting breast self-examination as early as possible then the life expectancy of 80-90% higher recovery. This study aims to determine the effectiveness of